Israeli Nurse Managers’ Organizational Values in Today’s Health Care Environment - Hendel, Tova (Nursing ethics, 2002)
The total value set of a working individual consists of three components: personal, professional and organizational values. In the light of the changing health care environment, the individual nurse manager’s values may no longer be applicable for coping with the needs of the work environment. For many nurses who developed their values in keeping with the humanistic tradition, the ‘new’ organizational values may create confusion, frustration and conflict. The purpose of this study was to determine if the organizational domain in the value sets of Israeli middle nursing managers in acute care hospitals reflect the process of shifting values needed in today’s management roles. Analysis of the results revealed that head nurses did not yet fully internalize the ‘new’ organizational values. Implications of the results for planning undergraduate and graduate programmes are detailed.